Transversal Skills in the Academic Curriculum of Management School Students in Algeria - Amghar Meryem; Naga Nahla; Zouambi Anaïs Radja (Economics and Business)
In a context of higher education reform, non-technical skills have gained a particular status as they are now placed at the core of educational programmes. This article aims to understand the involvement of higher education institutions (HEIs) and students in acquiring and developing non-technical skills. Accordingly, we conducted a quantitative survey among students at a management school. The results of this study suggest that students play an active role in their own skill development by engaging in scientific clubs, associations, and teamwork. However, this may not be sufficient to ensure better learning of cross-cutting skills, and higher education institutions must intervene by creating an environment conducive to this growth.